Pure XY gonadal dysgenesis. Swyer syndrome. "Two sides of the coin" - Protzel, Ana (2015)
The Swyer syndrome or pure XY gonadal dysgenesis is a disorder of the sex chromosomes and sexual differentiation, characterized by a phenotypically female individual with primary amenorrhea and lack of secondary sexual characteristics. The report of two cases diagnosed in the Department of Genetics at the National Hospital Edgardo Rebagliati Martins, aims to review recent reports of this rare disease diagnoses and treatment parameters that can prevent complications described.